Synergistic Effect of Calcium Chloride and Chitosan Treatment on Physicochemical Characteristics of Pineapple (Ananas Comosus) Fruit During Cool Storage: Life Sciences-Biotechnology for prospective medical science - Minh Phuoc Nguyen (International Journal of Life Science and Pharma Research, 2022)
Pineapple (Ananascomosus) is one of the most popular agricultural products in the world. It is well-known for its excellent flavour and taste, diversified valuable nutritional components as well as phytochemical and antioxidant properties. However it is quite perishable at ambient condition due to its high respiration rate. It is essential to find an appropriate strategy to extend its stability during storage. This study concentrates on the effectiveness of calcium chloride and chitosan treatments on the post-harvest physicochemical quality of pineapple during storage at 12oC and 80±5% relative humidity. The fruit was treated with different concentrations of CaCl2 (0.5%, 1.0%, 1.5%, 2.0%, 2.5%) via dipping for 4 min and chitosan (0.5%, 1.0%, 1.5%, 2.0%, 2.5% w/v) via coating. Different physicochemical parameters such as weight loss (%), firmness (N), decay percentage (%), total soluble solid (oBrix), ascorbic acid (mg/100g) were thoroughly examined, Our results showed that a combination of 2.0% CaCl2 with 1.5% chitosan created a synergistic effect on physicochemical characteristics of pineapple fruit during 14 days of cool storage. These results implied that calcium chloride combined with chitosan as edible coatings have potential to maintain fruit quality in respect of weight loss, firmness, total soluble solid, ascorbic acid while reducing post harvest spoilage (decay) in pineapple fruit.